Analysis Calculating of Hospital Labor Requirements Using the Workload Analysis Method - Noor, Hesty Latifa; Ridzuan, Ilyas Syafiq Darul; Isnaini, Vina Januar (Global Health Science Group, 2024)
In the era of changes in hospitals from implementing manual systems to more modern hospitals with digital systems, this has had many impacts, including reducing the need for labor in several departments. Or another option is to move human resources to other jobs that still require human workers in the work in that unit. Hospitals must wisely shift their human resources work so as not to drastically reduce human resources. Results: Total time Norm = 34 Minutes,Working hours available = 133.920 minutes / year, and Calculating Standard Work Load (Working hours available / Total time Norm ) = 868.248. Meeting Supporting Task Factors = 29,57%, Training Supporting Task Factors = 5,38%, Total Supporting Task Factors = 29,57% + 5,38% = 34,95%, Supporting Task Standards = 1,54. Total Energy Requirements 3.40, Supporting Task Standard 1.54, Human resource requirements 5.24 (Rounding 5). Conclusions: Based on the results of research at the hospital, in the file scan section, there were 2 officers. The results of calculating human resource needs at the Hospital in the file scan section using the Health Workload Analysis (ABK Kes) method resulted in a total of 5 staff, whereas currently only 2 staff are available so an additional 3 people are needed.